2017
DOI: 10.4172/2161-1122.1000439
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship between Diabetes Mellitus and Tooth Loss among Diabetic Patents in Garki General Hospital Garki Abuja, Fct Nigeria

Abstract: Study background: This research is to assess the number of missing teeth and to examine the relationship between age and tooth-loss in diabetic patients. Methods:The study consisted of 201 diabetic patients and an equal number of non-diabetic patients as control. Self-administered questionnaires were distributed which contained close-ended questions and this was followed by an oral examination of each patient; number of missing teeth were recorded in a data collecting sheet. Data was evaluated using SPSS 20 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(23 reference statements)
3
2
1
Order By: Relevance
“…Fortunately, the percentages are still considerably high. The similar trend was also seen in the study of Ikimi et al, (2018) [ 19 ]. They found 84.3% of Nigerian physicians agreed on the effect of periodontitis on the blood sugar control.…”
Section: Discussionsupporting
confidence: 89%
“…Fortunately, the percentages are still considerably high. The similar trend was also seen in the study of Ikimi et al, (2018) [ 19 ]. They found 84.3% of Nigerian physicians agreed on the effect of periodontitis on the blood sugar control.…”
Section: Discussionsupporting
confidence: 89%
“…Also, the correlation between the systemic health status of the patients and the number of missing teeth was found to be statistically signi icant. This is in agreement with previous study by (Ikimi et al, 2017), where statistically signi icant correlation was observed between the systemic health status of the patients and the number of missing teeth.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, research conducted by Ikimi et al [9] conducted in FCT Abuja, Nigeria shows a significant increase in tooth decay with subsequent tooth loss in addition with symptoms of periodontal disease among diabetic patients than non-diabetic, which is also in line with our research that shows a positive correlation between diabetes mellitus and periodontal diseases. In addition, Molina et al, [10] reported that diabetes mellitus may be considered among the risk factor for the appearance of periodontal disease.…”
Section: Discussionsupporting
confidence: 92%